Local foods systems and community economic development. Issue 5 (20th October 2017) - Deller, Steven C.; Lamie, David; Stickel, Maureen
Abstract: Local food system development is a popular strategy employed by many communities in the pursuit of sustainable and equitable economic growth and development. This often includes a range of economic projects including farmers markets, community supported agriculture enterprises, urban farming/agriculture projects, and food hubs. Sometimes it includes intermediated marketing channels like grocery stores and broad-line distributors interested in providing local foods. Despite growing prominence in the policy arena, many of the presumptions of the local food movement remain largely untested. This review provides critical analysis of current research on local and regional food networks and reveals that much of this research currently lacks strong theoretical grounding and quantitative rigor. As community development practitioners and planners play an important role in food system design, organization, policy, and implementation in an effort to produce community or regional wellbeing, it is important for them to distinguish between objective, research-based information and speculative, advocacy-oriented analysis.